Yuzhnoye's new liquid rocket engines as enablers for space exploration. (October 2016) - Degtyarev, Alexander; Kushnaryov, Alexander; Shulga, Vladimir; Ventskovsky, Oleg
Abstract: Advanced liquid rocket engines (LREs) are being created by Yuzhnoye Design Office of Ukraine based on the fifty-year experience of rocket engines' and propulsion systems' development. These LREs use both hypergolic (NTO+UDMH) and cryogenic (liquid oxygen+kerosene) propellants. First stage engines have a range of thrust from 40 to 250 t, while the upper stage (used in space) engines - from several kilograms to 50 t and a re-ignition feature. The engines are intended for both Ukraine"s independent access to space and international market. Highlights: Advanced liquid rocket engines being created by Yuzhnoye of Ukraine are presented. The engines use hypergolic (NTO+UDMH) and cryogenic (LOX/kerosene) propellants. 1st stage engines thrust: 40 t to 250 t, upper stage: few kg to 50 t, re-ignitable. Upper stage engines could efficiently serve deep space exploration programs. Yuzhnoye rich experience allows to substantially reduce development costs.